Kappa Opioid Receptor Blockade in the Amygdala Mitigates Pain Like-Behaviors by Inhibiting Corticotropin Releasing Factor Neurons in a Rat Model of Functional Pain - Yakhnitsa, Vadim; Ji, Guangchen; Hein, Matthew; Presto, Peyton; Griffin, Zack; Ponomareva, Olga; Navratilova, Edita; Porreca, Frank; Neugebauer, Volker (Frontiers in Pharmacology, 2022)
Functional pain syndromes (FPS) occur without identifiable tissue injury or noxious events and include conditions such as fibromyalgia, migraine, and others. Stressors are very common triggers of pain attacks in various FPS conditions. Recent evidence suggests that kappa opioid receptors (KOR) in the central nucleus of amygdala (CeA) contribute to FPS conditions, but underlying mechanisms remain to be determined. The CeA is rich in KOR and also encompasses the major output pathways through projection neurons that include corticotropin releasing factor (CRF) expressing neurons. Here we tested the hypothesis that KOR blockade in the CeA in a rat model of FPS reduces pain-like and nocifensive behaviors by restoring inhibition of CeA-CRF neurons. Intra-CeA administration of a KOR antagonist (nor-BNI) decreased mechanical hypersensitivity and affective and anxiety-like behaviors in a stress-induced FPS model. In systems electrophysiology experiments in anesthetized rats, intra-CeA application of nor-BNI reduced spontaneous firing and responses of CeA neurons to innocuous and noxious mechanical stimuli. In brain slice whole-cell patch-clamp recordings, nor-BNI increased feedforward inhibitory transmission evoked by optogenetic and electrical stimulation of parabrachial afferents, but had no effect on monosynaptic excitatory transmission. Nor-BNI decreased frequency, but not amplitude, of spontaneous inhibitory synaptic currents, suggesting a presynaptic action. Blocking KOR receptors in stress-induced FPS conditions may therefore represent a novel therapeutic strategy.